Gold and hypervalent iodine(iii): liaisons over a decade for electrophilic functional group transfer reactions - Banerjee, Somsuvra; Bhoyare, Vivek W.; Patil, Nitin T. (Chemical Communications, 2020)
Over the last two decades, hypervalent iodine(iii) reagents have evolved from being `bonding curiosities' to mainstream reagents in organic synthesis, in particular, electrophilic functional group transfer reactions. In this context, gold catalysts have not only emerged as a unique toolbox to facilitate such reactions (especially alkynylations) but also opened new possibilities with their different modes of reactivities for other functional group transfer reactions (acetoxylations and arylations). This feature article critically summarizes hitherto all such Au-catalyzed electrophilic functional group transfer reactions with hypervalent iodine(iii) reagents, emphasizing their mechanistic aspects.